Risk Management Analysis of Mobile JKN Queues for Outpatients at Islamic Hospital Surabaya With a Failure Mode Effect and Analysis Approach - Rivan Virlando Suryadinata Suryadinata; Vip Paramarta; Budhi Setiato Setiato; Agus Aan Adriansyah (Jurnal Ilmiah Kesehatan, 2026)
The utilization of Mobile JKN at RSRS shows an increasing trend, although it has not yet reached optimal levels. Various risks have been identified from both patient and operational perspectives, including limited digital literacy, registration errors, inappropriate arrival times, as well as technical issues in the system and supporting services. Analysis using the Failure Mode and Effects Analysis (FMEA) method with parameters of severity, occurrence, and detection produced Risk Priority Number (RPN) values to determine risk priorities. The results indicate that the dominant influencing factors are physician delays, limited access to technology, and patient non-compliance. These findings serve as a basis for formulating improvement recommendations to enhance the efficiency, effectiveness, and quality of Mobile JKN services in hospitals. This study also shows that the implementation of Mobile JKN at RSRS has been relatively effective, with a user-friendly and well-integrated system that contributes to improved service efficiency and reduced waiting times. However, its utilization remains suboptimal due to patient-related factors, particularly low digital literacy and non- adherence to schedules. A total of nine risks were identified, with an average score of 19.5, which was successfully reduced to 12.5 after interventions such as patient education, system strengthening, and queue management. These results highlight that a combination of educational approaches, technological enhancement, and consistent operational management is essential to optimize the sustainable utilization of Mobile JKN.